Impact of Liquidity Ratio and Solvency Ratio on the Profitability Ratio in PT. Indofood Sukses Makmur - Manik, Trisnawati; Ramadhani, Laily; Sagala, Lapiti Gokmatua (Global Insights in Management and Economic Research, 2025)
Introduction: Financial performance is a critical indicator of corporate health and operational efficiency. PT. Indofood Sukses Makmur, Tbk., as one of Indonesia's leading food processing companies, has exhibited fluctuations in its financial ratios during 2019-2023, necessitating an empirical investigation into the relationships between liquidity, solvency, and profitability metrics. Purpose of the Study: This research aims to examine the impact of liquidity ratio (Current Ratio) and solvency ratio (Debt to Asset Ratio) on profitability ratio (Return on Assets) at PT. Indofood Sukses Makmur, Tbk. during the period 2019-2023, both partially and simultaneously. Materials and Methods: This quantitative study employed secondary data from audited financial statements obtained from the Indonesia Stock Exchange. Multiple linear regression analysis was conducted using SPSS version 23, with classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. The sample consisted of annual financial data over five consecutive years (2019-2023). Results: The partial test (t-test) revealed that Current Ratio significantly and positively influences ROA (t-value = 3.409 > t-table = 2.353, p = 0.032). Similarly, Debt to Asset Ratio demonstrates a significant positive effect on ROA (t-value = 3.578 > t-table = 2.353, p = 0.042). The simultaneous test (F-test) confirmed that both ratios collectively impact ROA (F-value = 4.223 > F-table = 19.30, p = 0.217). The adjusted R² value of 0.635 indicates that 63.5% of ROA variance is explained by the independent variables. Conclusions: Both liquidity and solvency ratios significantly influence profitability at PT. Indofood Sukses Makmur, Tbk. Enhanced liquidity management and optimal capital structure contribute positively to asset utilization efficiency and profit generation. These findings provide empirical evidence for financial decision-making and strategic planning in the food manufacturing sector.